Detection of heterozygous mutation in hook microtubule-tethering protein 1 in three patients with decapitated and decaudated spermatozoa syndrome. Issue 3 (12th January 2018) - Chen, Huixing; Zhu, Yong; Zhu, Zijue; Zhi, Erlei; Lu, Keming; Wang, Xiaobo; Liu, Feng; Li, Zheng; Xia, Weiliang
Abstract : Background: The mechanism of intramanchette transport is crucial to the transformation of sperm tail and the nuclear condensation during spermiogenesis. Although few dysfunctional proteins could result in abnormal junction between the head and tail of spermatozoon, little is known about the genetic cues in this process. Objective: Based on patients with severe decapitated and decaudated spermatozoa (DDS) syndrome, the study aimed to validate whether new mutation exists on their Hook microtubule-tethering protein 1 ( HOOK1 ) genes and follow their results of assisted reproduction treatment (ART). Methods: 7 severe teratozoospermia patients with DDS (proportion >95%) and three relative members in one pedigree were collected to sequence the whole genomic DNA. The fertilisation rates (FRs) of these patients were followed. Morphological observation and interspecies intracytoplasmic sperm injection (ICSI) assays were applied. Results: A novel missense mutation of A to G (p.Q286R) in patients with DDS (n=3/7) was found in the HOOK1 gene, which was inherited from the mother in one patient. This variant was absent in 160 fertile population-matched control individuals. Morphological observation showed that almost all the DDS broke into decaudated heads and headless tails at the implantation fossa or the basal plate. The clinical studies indicated that the mutation might cause reduced FRs on both ART (FR=18.07%) and interspecies ICSI (FR=16.98%). Conclusions: An unreported mutation in HOOK1 gene was identified, which might be responsible to some patients with DDS. Further studies need to uncover the molecular mechanism of spermiogenesis for genomic therapy.